Draw insects - DuBosque, D. C. ([Columbus, N.C.] : Peel Productions, 1998)
Provides step-by-step instructions for drawing insects, including the bumblebee, giant beetle, and yellow jacket.
Includes index.
Keywords: Insects in art -- Juvenile literature; Drawing -- Technique -- Juvenile literature; Insects in art; Drawing -- Technique